P296 HIDDEN PERICARDIAL CONSTRICTION IN A PATIENT WITH CHRONIC PERICARDIAL EFFUSION AND "UNEXPLAINED" DYSPNEA. (18th May 2022) - Caravita, S; Baratto, C; Ghiso, P; Torlasco, C; Senni, M; Sganzerla, P; Perego, G; Badano, L; Parati, G
Abstract: Constrictive physiology leads to exertional symptoms related to restrained diastolic filling and intracardiac/intrathoracic dissociation. However, these hemodynamic abnormalities might not be evident in some patients. A 55–year–old woman was referred to our center to perform a right and left cardiac catheterization because of "unexplained" dyspnea. Three years before she was found to have a large idiopathic pericardial effusion. Anti–inflammatory therapy did not result in any improvement. Since then, the patient complained dyspnea NYHA II–III, in the absence of any clinical and imaging sign of tamponade/pericardial constriction. At rest, there was no sign of constriction, but a relative hypovolemic status characterized by low pulmonary and filling pressures and cardiac output (CO) at the lower limits of normal. After a 500 mL saline load and passive legs raising, Kussmaul's and "M" signs appeared on the right atrial pressure curve (Figure 1 ), the pulmonary artery wedge pressure (PAWP) – left ventricular end–diastolic pressure (LVEDP) gradient difference between expiration and inspiration was >5 mmHg (Figure 2 ), and ventricular systolic pressures went out of phase by 180°. Both right and left filling pressures as well as pulmonary pressures steeply increased in a concordant manner by about 10 mmHg after fluid load, in absence of a relevant increase in CO (Figure 3 ). Physical exercise performed thereafter showed an additional mild increase with a plateau pattern of all pressures, suggesting an upward–shift of the pressure/flow relationship (Figure 3 ). All these signs suggested a latent constrictive physiology. Despite this, the patient showed an optimal CO reserve coupled with a normal exercise capacity (peak oxygen consumption, VO2, 127% of predicted) that would have argued against our hypothesis. We then performed a diagnostic and evacuative pericardiocentesis. After the drainage of 130 ml of pericardial fluid, LV transmural pressure increased and CO at rest was fully normalized. Moreover, no hemodynamic sign of constriction could be observed even after a 1000 ml saline load. The patient reported disappearance of exertional breathlessness, objectivated by an increase in peakVO2 by 20% as compared with the previous test. Thus, our case underscores how subtle the hemodynamic impact of pericardial effusion can be, with the need of well–tailored diagnostic exams to explain otherwise "unexplained" patients' symptoms, with potential therapeutic implications.